Outcome and Tips of the December Readings in Memory of S.B. Barngolts’2024 - I. F. Vetrova; M. V. Melnik (Учёт. Анализ. Аудит, 2025)
This paper analyzes the fundamental stages of economic analysis and control, emphasizing the methods and techniques of accounting, control, and analytical processes in today’s rapidly strengthening environment of innovation, organizational change, and economic interrelationships. The authors substantiated dominant trends of the accounting growth, analysis and control at the current stage of economic transformation as one of the major management functions aimed at providing it with reliable, comprehensive and sufficient information. This is necessary for an objective assessment of the state of the object, determining priority areas of its progress and forming long-term strategies for the main levels and spheres of economic transformation. The study systematized the key scientific approaches to improving all stages of accounting, analytical, and control activities, considering the methodological unity of the main directions and stages of this process at different management levels. Because accounting and reporting practices vary widely, comparing and organizing their development is crucial for effective improvement and adaptation to economic change. The purpose of the research is to systematize scientific developments and practical experience of leading Russian organizations in accounting, analysis, control, and audit. The work assesses the level of standardization and regulatory framework for accounting and control processes, and substantiates new types of analytical work in digitalization of the economy and the use of new intelligent analysis methods. Methodology. The paper is based on the analysis and assessment of scientific research and practical experience in accounting, analysis, and control (audit). This work emphasizes the integration of methodologies and techniques for their organization across all management levels in organizations with varying legal structures, which promotes consistent, mutually beneficial collaboration and improves national economic productivity. Conclusions. The study and comparison of the major areas of improving accounting, analysis and control (audit) allows to determine the most effective areas of their development. Also, this process provides objectively assesses the importance of standardizing these processes and highlights the specifics corresponding to the features of the technological and organizational characteristics of distinct areas of activity and tasks solved at different levels of management.